Yoga, change and embodied enlightenment - Langøien, Lars (Approaching Religion, 2012)
Though it has been claimed that modern yoga retains little of its origins of religious austerity, I will argue that even if yoga as a physical practice has taken a strong position among the modern fitness trends, there are still important links to the philosophical and religious traditions of India – not least in the minds of many of its practitioners. Reorientations of these traditions to more modern settings have an impact on the practitioners’ bodies, and the embodied experience of the practice in turn influences yoga.